2022
DOI: 10.2166/aqua.2022.080
|View full text |Cite
|
Sign up to set email alerts
|

Mixing of Fe3O4 nanoparticles under electromagnetic and shear conditions for wastewater treatment applications

Abstract: The ability of heavy metals to accumulate in living organisms, combined with the fact that they are not biodegradable, necessitates an expansion and improvement of the existing water purification methods. An effective mixing of contaminated water with heavy metals and magnetic nanoparticles is crucial for water treatment applications. In the present work, electromagnetic and shear mixing are combined to explore optimization mixing strategies. Mixing is studied through simulations under various initial conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The new transformed equations are, β„Ž 𝑛 (𝛿𝑙 𝑛 + 𝛿𝑙 π‘›βˆ’1 ) = (π‘Ÿ 5 ) 𝑛 (39) The equations are given below in their condensed form, once more utilizing equations (35)(36)(37)(38)(39) in equations (30)(31)(32)(33); Recalling the precise boundary conditions without iteration, we take steps to make sure that these correct values are preserved across all iterations.…”
Section: Computational Scheme and Solution Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The new transformed equations are, β„Ž 𝑛 (𝛿𝑙 𝑛 + 𝛿𝑙 π‘›βˆ’1 ) = (π‘Ÿ 5 ) 𝑛 (39) The equations are given below in their condensed form, once more utilizing equations (35)(36)(37)(38)(39) in equations (30)(31)(32)(33); Recalling the precise boundary conditions without iteration, we take steps to make sure that these correct values are preserved across all iterations.…”
Section: Computational Scheme and Solution Methodologymentioning
confidence: 99%
“…Rajesh et al [37] analyzed the exact analytical solutions of hybrid nanofluid flow for heat transfer characteristics along the vertical infinite surface with ramped-temperature. Liosis et al [38] studied the combined form of shear and electromagnetic mixing to compute optimization mixing strategies under various initial conditions. The Carreau nanofluid phenomenon for concentration and heat characteristics with variable properties effects along stretchable surface has been considered in [39].…”
Section: Introductionmentioning
confidence: 99%
“…Hejazian and Nguyen [27] demonstrated that a non-uniform magnetic field in the Y-channel between deionized (DI) water and ferrofluid led to secondary flow, and higher ferrofluid concentration was more effective in mixing. A magnetic field-driven active mixer could also be applied to purify the water by mixing nanoparticles, which can capture the heavy metal with the water [28][29][30][31]. These active methods enhance the mixing performance rapidly, but need additional force or energy generation devices, as well as complex control and detecting systems.…”
Section: Introductionmentioning
confidence: 99%